Early selection of late-flowering almonds - Dicenta F.; Ortega E.; García-Gusano M.; Martínez-Gómez P. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
The aim of the study was to discover the possibilities of an early selection of those seedlings with late flowering in relation to germination of seeds or leafing time in the following year. The crosses were conducted in 1997. The seeds obtained were germinated by conventional stratification at 7 degrees C, and the number of weeks necessary for the germination of each seed recorded. The trees were planted in 1998. Between 1999 and 2002 their leafing time was recorded, and in 2001 and 2002 also their flowering time. The results indicated that within each family, the correlations between these characteristics were not important and, in most cases, not significant. In our opinion, to obtain seedlings with an extra-late flowering time, the selection of parents with very late flowering time is essential, with subsequent selection of the seedlings during their first flowering.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)